Problematika Siswa Dalam Mempertahankan Konsentrasi Belajar Pada Mata Pelajaran SKI Kelas VII Di Mtsn 7 Agam - Ridho Maulana; Junaidi . (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
This study aims to examine: (1) forms problem solving experienced by students in maintaining concetration in learning on the subject of skiing in grade VII at MTsN 7 Agam. (2) what efforcts have teachers made to over come student problems in maintaining concentration in learning on the subject of skiing in grade VII at MTsN 7 Agam. Data collection was conducted through observation, interview, and documentation metods. The collected data were analyzed using data reduction, verification and conclusion drawing techniques. The findings of the study indicate that. (1) Froms of problem solving experienced by students in maintaining concentration in learning include: students talking to their deskmates during the learning process, sleeping during class, putting their heads on the table, scribbling on paper, looking for materials for toys or looking for activities, being nosy or disturbing friend, being late to class after recess, playing with cellphones, asking permission to go to the bathroom, and learning against the wall. (2) What efforts do teachers make to overcome student’s problems in maintaining concentration in learning on the subject of the subject: by praying at the beginning of each lesson giving reprimands, teachers provid story stimulation, apply the marketing place method, become role models for students, transfer religious values, organize religious activities, provide motivation, establish communication between tearchers, students, and parents, pay attention to student behavior, and control technological progress.